Acute effects of passive static stretching on the vastus lateralis muscle architecture of healthy young men - Eurico Peixoto César; Letícia de Oliveira Teixeira; Daniel Vieira Braña Côrtes de Souza; Paulo Sergio Chagas Gomes (Universidade Federal de Santa Catarina, 2017)
The aim of the study was to investigate the acute effects of passive static stretching (PSS) on the fascicle length (FL) and fascicle angle (FA) of the vastus lateralis muscle (VL) in two different joint positions. Twelve physically active men (26.9 ± 7.5 years, 178.6 ± 7.0 cm, and 82.5 ± 16.8 kg) were placed in the prone position for the acquisition of ultrasound images (US) of VL, registered with extended and totally flexed knee up to the heel contact with the gluteus, before and after a PSS routine comprised of three 30-s repetitions maintained in the maximal discomfort position as reported by the participant. Results of the paired t-test indicated an increase in FL (16.2%; p = 0.012) and reduction in FA (15.5%; p = 0.003) in pre vs. post stretching comparisons for the extended knee position. There was also a significant increase in FL (34%; p = 0.0001) and reduction in FA (25%; p = 0.0007) when compared the extended knee vs. flexed knee positions. There were no significant differences in muscle architecture variables for the flexed knee position. The results showed high and moderate correlation of FL and FA for the extended (r = -0.89 and r = -0.74) and flexed knee (r = -0.76 and r = -0.78) position, pre and post stretching, respectively. It was concluded that the static stretching acutely affects the vastus lateralis muscle architecture only in the extended knee position, but not in the flexed knee position.